2015
DOI: 10.1002/bies.201400166
|View full text |Cite
|
Sign up to set email alerts
|

Blood and immune cell engineering: Cytoskeletal contractility and nuclear rheology impact cell lineage and localization

Abstract: Summary Clinical success with human hematopoietic stem cell (HSC) transplantation establishes a paradigm for regenerative therapies with other types of stem cells. However, it remains challenging to repair or replace tissues after engineering stem cells in vitro. Recent studies suggest that stem cells sense physical features of their niches. Here we review biophysical contributions to lineage decisions, maturation, and trafficking in the hematopoietic system. Polarized cellular contractility and nuclear rheolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Micropipette aspiration of embryonic stem cells and adult stem cells shows that due to lack of lamin A/C their nuclei are much softer than those of differentiated epithelial cells (Pajerowski, Dahl, Zhong, Sammak, & Discher, 2007). In the early 2000s, the proteins of the LINC (linker of nucleoskeleton and cytoskeleton) complex, responsible for linking the cytoskeleton in the cytoplasm to nuclear lamins (Lamin A/C and Lamin Shivashankar, 2008;Pajerowski et al, 2007;Shin et al, 2013;Shin & Discher, 2015;Swift et al, 2013;. However, for a mechanical load applied to the cell surface, how the load is transduced into gene transcription has remained unclear for years.…”
Section: Prestress In Nuclear Mechanotransductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micropipette aspiration of embryonic stem cells and adult stem cells shows that due to lack of lamin A/C their nuclei are much softer than those of differentiated epithelial cells (Pajerowski, Dahl, Zhong, Sammak, & Discher, 2007). In the early 2000s, the proteins of the LINC (linker of nucleoskeleton and cytoskeleton) complex, responsible for linking the cytoskeleton in the cytoplasm to nuclear lamins (Lamin A/C and Lamin Shivashankar, 2008;Pajerowski et al, 2007;Shin et al, 2013;Shin & Discher, 2015;Swift et al, 2013;. However, for a mechanical load applied to the cell surface, how the load is transduced into gene transcription has remained unclear for years.…”
Section: Prestress In Nuclear Mechanotransductionmentioning
confidence: 99%
“…Numerous studies have shown that nuclear mechanics plays an important role in nuclear structures and function, nuclear lamins behave like mechanosensors, and the nucleus is a prestressed structure (Alisafaei, Jokhun, Shivashankar, & Shenoy, 2019 ; Banerjee, Bhattacharya, & Shivashankar, 2006 ; Banigan, Stephens, & Marko, 2017 ; Chambliss et al, 2013 ; Guilluy et al, 2014 ; Ho, Jaalouk, Vartiainen, & Lammerding, 2013 ; Irianto, Pfeifer, Ivanovska, Swift, & Discher, 2016 ; Jain, Iyer, Kumar, & Shivashankar, 2013 ; Kim et al, 2017 ; Kim, Hah, & Wirtz, 2018 ; Kim & Wirtz, 2015 ; Kirby & Lammerding, 2018 ; Lammerding et al, 2006 ; Lee et al, 2007 ; Mazumder, Roopa, Basu, Mahadevan, & Shivashankar, 2008 ; Pajerowski et al, 2007 ; Shin et al, 2013 ; Shin & Discher, 2015 ; Swift et al, 2013 ; Swift & Discher, 2014 ). However, for a mechanical load applied to the cell surface, how the load is transduced into gene transcription has remained unclear for years.…”
Section: Cytoskeletal Prestress In Mechanotransductionmentioning
confidence: 99%
“…Inside of the cell, myosin motors, cytoskeletal linking, polymerizing and regulating elements, cytoskeletal filaments, caveolae, the transcriptional cofactors YAP/TAZ, the nuclear lamina including lamins A and B and other signaling molecules are potentially parts of the mechanosensing process [132] , [477] . Of these candidates, particularly the role of YAP/TAZ, lamins and non muscle myosins was investigated in HSPCs in more detail [462] , [480] , [481] , [482] , [483] . Shin et al showed that non muscle myosin II plays an important role in sensing of the niche and polarized divisions by HSPCs [462] .…”
Section: Biophysical Signals Transmitted By the Ecm In Hsc Nichesmentioning
confidence: 99%